Karakteristik Bio-Briket Berbahan Baku Batu Bara dan Batang/Ampas Tebu terhadap Kualitas dan Laju Pembakaran - Nurhalim Nurhalim; Rochim Bakti Cahyono; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2018)
Indonesia has a very large fossil fuel source such as coal. In Indonesia, almost all power plants and industries use coal as solid fuel. Burning coal produces fly ash, bottom ash, poisonous gas and unused coal residue. The coal waste is commonly found in mining operations, abandoned mining areas, laboratories and power plants. This problem could be solved by producing bio-briquette using the coal waste. In this study, laboratory scale pyrolysis and non pyrolysis methods were used to produce bio-briquette using the coal waste with measurement of proximate analysis and burning rate. Pyrolysis was carried out at constant temperature of 400 oC for 2 hours. The total weight of briquette sample as much as 99.87 g was burnt at 400 oC with sufficient air space in the furnace. The waste coal was mixed with biomass bagasse and sugar cane stems before the briquetting process. The composition of the briquette material was 50 g of coal waste, 30 g of sugar cane biomass, and 10 g of bagasse. To form the briquette, tapioca was used as adhesive in addition to 5 g of clay with 50 mesh of size and application of 50 kg/cm2 pressure. The result of proximate analysis and combustion of the non-pyrolysis bio-briquette showed that non-pyrolysis bio-briquette contained 4.17 % of moisture content, 18.39% of fly ash, 25.56% of ash content, 5157.87 cal/g of calorific value. The mass of of pyrolysis bio-briquette (50 g) decreased to 30 g during 30 minutes, the compulsion reached maximum speed on 1.93 g/s and the smoke disappeared on the 24th minute The pyrolysis process on coal waste decreased the smoke and the addition of biomass increased the calorific value of bio-coal briquette.ABSTRAKIndonesia memiliki sumber energi fosil yang sangat besar seperti batu bara. Hampir seluruh pembangkit listrik dan industri di Indonesia menggunakan bahan baku batu bara. Batu bara memiliki limbah berupa flying ash, bottom ash, gas beracun dan sisa batu bara yang tidak terpakai. Limbah batu bara tidak terpakai banyak terdapat di pertambangan yang masih beroperasi, sisa lahan pertambangan, laboratorium, pembangkit listrik, sehingga perlu penanganan yang tepat seperti pembuatan briket bio-batu bara. Pada pembuatan briket bio-batu bara ini, batu bara diproses menggunakan metode pirolisis dan tanpa pirolisis dengan uji skala laboratorium seperti uji proksimat dan laju pembakaran. Proses pirolisis menggunakan suhu 400 oC selama 2 jam dan karbonisasi biomassa tanpa menggunakan parameter suhu dan waktu. Berat sampel briket sebesar 99,87 g dibakar pada suhu pembakaran 400 oC dengan menggunakan udara ruang didalam furnace. Sebelum proses pembriketan, batu bara yang telah mengalami proses pirolisis dan tanpa pirolisis dicampur dengan limbah biomassa ampas dan batang tebu. Variabel penelitian menggunakan 50 g limbah batu bara, 30 g biomassa batang tebu dan 10 g ampas tebu. Briket bio-batu bara menggunakan perekat tepung kanji dan tanah liat dengan berat masing–masing 5 g. Sedangkan untuk tingkat kelembutan setiap bahan briket adalah 50 mesh dengan kuat tekan 50 kg/cm2. Hasil analisis proksimat briket bio-batu bara PP (50 g) mengandung kadar air sebesar 4,17%, zat terbang 18,39%, kadar abu 25,56%, nilai kalori sebesar 5157,87 kal/g. Briket bio-batu bara PP (50 g) mengalami penurunan massa sebanyak 30 g selama 30 menit, laju pembakaran mencapai kecepatan maksimum 1,93 g/s dan asap hilang pada menit ke-24. Batu bara dengan proses pirolisis dapat menurunkan asap dan penambahan biomassa dapat menaikkan nilai kalori briket bio-batu bara.